Diferentes sustancias nutritivas en el cultivo de pimiento (Capsicum annuum) en sustrato de cascarilla de arroz más arena de río - Valverde Aguilar, Jorge Antonio (2015)
This research took place at San Antonio farm, located at community La Laguna, Ventanas, Los Rios province, whose coordinates are S 1° 26´ 34” y W 79°26’54”, 27 MAMSL. In order to evaluate nutrients on a capsicum (Capsicum annuum) plantation with rice husk substrate and river sand, a Completely Randomized Design with four treatments and four replications was used, on a 0, 30 m X 8, 0 m. plot. The experiment lasted 120 days. Evaluated treatments were: Treatment 1 Green Master (1.5 cc/L water), Treatment 2 Biotek (1.5 cc/L water), Treatment 3 Evergreen (1.5 cc/L water), Treatment 4 NPK (1.5 cc/L de water) –witness. Results: Evergreen treatment presents 22.30 cm, it means the plant highest tall, 7.94 mm, stem highest diameter, 10.10 cm, longest fruit, also; with 15.80 the fruit highest diameter. The plot performance was the best, presenting 4.80 kg. About yield per hectare, the T3 (Evergreen) treatment shows the best results: 36.888,89 kg. About production costs; the highest expense was presented by T2 (Biotek) treatment: USD 19.976,62. The best Cost – benefit ratio was presented by T3 (Evergreen treatment), with a 1, 38 value.